The Acceptance Technology Model for Adoption of Social Media Marketing in Jabodetabek - Adeline Hope Pranoto; Paul Lumbantobing (Bina Nusantara University, 2021)
The research aimed to find out the influence and impacts of social media marketing (SMM) in promoting micro, small, and medium enterprises (MSMEs) in Indonesia. The approach of research was a quantitative research with data collection method using electronic questionnaires of Google forms obtaining 163 respondents who were owners of MSMEs in Jakarta and Tangerang. The measurement model of outer and inner model was analyzed by SmartPLS software. Structural Equation Model was being used to test the relations of each construct. The findings show that SMM positively mediates: 1) the relationship between perceived usefulness and impact on business; 2) the relationship between perceived ease of use and impact on business; 3) the relationship between compatibility and impact on business; 4) the relationship between cost and impact on business, which conclude that SMM has positive impacts on business. On the other hand, SMM negatively mediates the relationship between facilitating conditions and impact on business. The research implies that the adoption of social media marketing by MSMEs is encouraged by such factors as usefulness, ease of use, compatibility, and cost. Hence, it is advisable that MSMEs facilitate the employees with technical infrastructures and training to increase productivity and performance.